Mirror movements in parkinsonism: evaluation of a new clinical sign - Espay, A J; Li, J-Y; Johnston, L; Chen, R; Lang, A E (Journal of neurology, neurosurgery and psychiatry, 2005)
Background: Mirror movements (MM) are not widely appreciated in parkinsonism and no report has evaluated this clinical sign in detail. Objectives: To define the parkinsonian clinical features associated with MM in patients with early, asymmetric parkinsonism. Methods: Twenty seven patients with early Parkinson’s disease were evaluated using a standardised videotaping protocol. MM were scored from blinded video assessment using a clinical scale that rates the amplitude, distribution, and proportion of mirroring in the less affected limb. Parkinsonian features were combined into axial and lateralised scores using related items of the Unified Parkinson’s Disease Rating Scale. Results: MM were present in 24 of 27 patients. There was a significant linear correlation between the degree of asymmetry of motor deficits and MM on the less affected side. The effect of asymmetry was greater when the proportional rather than the absolute motor difference between sides was largest. Asymmetry in leg rigidity was the most important examination feature in the prediction of contralateral foot mirroring. Conclusions: MM are a clinical feature of the unaffected or less affected side in mild asymmetric parkinsonism. Their presence may be a useful clinical finding in early parkinsonism.